COMPANY COMPETITIVENESS OPERATING IN THE MILK INDUSTRY - Timeridjine, Sara; Chitti, Mohand (The European Journal of Applied Economics, 2023)
In the face of globalization and its effects, the company’s competitiveness remains an essential element for their growth and survival. This contribution aims to shed light on competitive advantage as a source of company’s competitiveness, by analyzing the competitive intensity in the milk industry based on Porter’s competitive forces supported by a multiple case study of Bejaia companies operating in the Algerian milk industry. For this paper, we studied large private industries with more than 20 years of experience in their fields of activity and with a common cost strategy. The results of study showed that the competitive intensity in this industry is important and that the competitive advantage is governed by a set of cost and non-cost factors that allow the studied cases to strengthen their positions by relying on their competitive advantages.